Josefina San Martín Bacaicoa - Maraver Eyzaguirre, Francisco (Anales de Hidrología Médica, 2013)
Josefina San Martín Bacaicoa, after an ordinary competitive examination in 1986, became the fourth professor of Medical Hydrology in the history of the Spanish Universities. The period between her bachiller degree in Medicine and Surgery and that moment is dedicated to her professional medical practice, teaching and investigation which has always been related to her two medical specializations: Rehabilitation Therapy in Centro Nacional de Rehabilitación and Medical Hydrology within the Chair in Medical Hydrology of the Faculty of Medicine in the Complutense University of Madrid and in several spa establishments such as Panticosa, Arnedillo, San Juan de Campos and Molgas. Since she achieved the chair, she is solely dedicated to Hydrology and carries out an important role in associations, organization and internationalization related to this speciality. At the same time, she has constant academic activity in the Royal National Academies of both Medicine and Pharmacy where she is corresponding member since the years 1989 and 1996 respectively.
Keywords: Josefina San Martin; Medical Hydrology; Rehabilitation; Medical Specialization; University Chairs; Scientific Society; Medical Journals